Cost‐effectiveness of alternating magnetic resonance imaging and digital mammography screening in BRCA1 and BRCA2 gene mutation carriers. Issue 6 (26th November 2012) - Cott Chubiz, Jessica E.; Lee, Janie M.; Gilmore, Michael E.; Kong, Chung Y.; Lowry, Kathryn P.; Halpern, Elkan F.; McMahon, Pamela M.; Ryan, Paula D; Gazelle, G. Scott
Abstract BACKGROUND: Current clinical guidelines recommend earlier, more intensive breast cancer screening with both magnetic resonance imaging (MRI) and mammography for women with breast cancer susceptibility gene (BRCA) mutations. Unspecified details of screening schedules are a challenge for implementing guidelines. METHODS: A Markov Monte Carlo computer model was used to simulate screening in asymptomatic women who were BRCA1 and BRCA2 mutation carriers. Three dual‐modality strategies were compared with digital mammography (DM) alone: 1) DM and MRI alternating at 6‐month intervals beginning at age 25 years (Alt25), 2) annual MRI beginning at age 25 years with alternating DM added at age 30 years (MRI25/Alt30), and 3) DM and MRI alternating at 6‐month intervals beginning at age 30 years (Alt30). Primary outcomes were quality‐adjusted life years (QALYs), lifetime costs (in 2010 US dollars), and incremental cost‐effectiveness (dollars per QALY gained). Additional outcomes included potential harms of screening, and lifetime costs stratified into component categories (screening and diagnosis, treatment, mortality, and patient time costs). RESULTS: All 3 dual‐modality screening strategies increased QALYs and costs. Alt30 screening had the lowest incremental costs per additional QALY gained (BRCA1, $74, 200 per QALY; BRCA2, $215, 700 per QALY). False‐positive test results increased substantially with dual‐modality screening and occurred more frequently in BRCA2 carriers. Downstream savings in both breast cancer treatment and mortality costs were outweighed by increases in up‐front screening and diagnosis costs. The results were influenced most by estimates of breast cancer risk and MRI costs. CONCLUSIONS: Alternating MRI and DM screening at 6‐month intervals beginning at age 30 years was identified as a clinically effective approach to applying current guidelines, and was more cost‐effective in BRCA1 gene mutation carriers compared with BRCA2 gene mutation carriers. Cancer 2013. © 2012 American Cancer Society.